Designing Scientific Learning for Ecosystem Thematic Learning in Fifth Grade Primary School - Lutfan, Lutfan; Siregar, Eveline; Kustandi, Cecep (Jurnal Paedagogy, 2023)
This research aims to design instruction for ecosystem thematic learning with a scientific approach in fifth-grade primary school. This research used the development model of Lee and Owen (2004), consisting of the assessment, analysis, and design stages. Subjects in this research were fifth-grade primary school at SDN Pisangan Timur 11. The data was collected using observations and interviews, which showed that the learning outcomes of some students still had scores below the passing grade. In addition, the thematic ecosystem learning was not optimal; the learning media used had not helped students to understand ecosystem knowledge more deeply because it only used video support and PowerPoint from the teacher, and the learning strategies or methods used are boring too. This research concludes that learning design is possible to increase the grade of student learning outcomes. Second, the scientific approach model has the characteristics of "doing science". This approach can make it easier to improve the learning process.